The genus Pseudoxyethira Schmid (Trichoptera, Hydroptilidae) in Japan - Ito, Tomiko (Zootaxa, 2017)
The caddisfly genus Pseudoxyethira Schmid (Hydroptilidae) is revised for Japan. The male of a Japanese species, P. ishiharai (Utsunomiya 1994) is redescribed with new distribution records. A new species, P. funatsuki sp. nov., is described from the southernmost region of Japan. Pseudoxyethira thingana (Oláh 1989), known from Vietnam and southern China, is recorded from Japan for the first time, and its male is redescribed.